Identification of Candida Spp. Isolated From Urine by Phenotypic Methods and Multiplex Pcr in Duhok, Iraq - Mohammed, Ahmed B.; Ali, Jumma H.; Abdullah, Samir K. (Science Journal of University of Zakho, 2017)
The present study was aimed to isolate and identify Candida species from urine samples obtained from patients with urinary tract infection from Duhok province. Species identification was based on colony color on chromogenic Candida agar as well as multiplex PCR method. Results revealed the prevalence of non-albicans Candida. C.krusei was the most frequently isolated species with the prevalence of 26.3% followed by C.kefyr 23.68%, C.glabrata (18.42% and C.albicans 15.78%. Multiplex PCR method seemed to be more accurate and reliable for identification of Candida yeast.